Meaning and Order: Typology and Responses of Theodicy in Kouduo Richao - DONG, Yuzhi (Journal of Research for Christianity in China (JRCC), 2025)
In Kouduo Richao, missionaries provided theological explanations for suffering and offered compensatory promises for resolving suffering through forms of theodicy such as absolute obedience, human righteousness, otherworldly compensation, and Christology. The suffering that troubled believers ranged from personal misfortunes to social injustices on a collective level. Analyzing believers’ responses in Kouduo Richao reveals that their acceptance of theodicy was influenced by their social class and the dominant Confucian values of society. This also offers a glimpse into the distinctive spiritual lives of the community of literati-believers in late Ming China.